Vertical Distribution of Marine Wood Boring and Fouling Organisms from the Estuarine Areas of the South West Coast of India - SANTHAKUMARI, V; NAIR, N BALAKRISHNAN (Fishery Technology, 2017)
Vertical distribution of marine wood boring and fouling organisms from thre different estuarine areas namely, the Ernakulam channel in the Cochin Backwaters, Ayiramthengu in the Kayamkulam Lake and Neendakara in the Asthamudi Lake during the post-monsoon, the pre-monsoon and the monsoon periods is presented. The boring organisms noticed during the present study were Martesia striata, Teredo furcifera, Nausitora hedleyi and Sphaeroma terebrans. The dominant fouling organisms were Balanus amphitrite amphitrite, calcareous worms and Modiolus sp. Algae and diatoms were very common on the sub-tidal panels during the monsoon. The incidence of Teredo, Nausitora and calcareous tube worms were significantly high on the bottom panels. Sphaeroma, Balanus and Modiolus occurred in greater numbers on the intertidal panels.